1997
DOI: 10.1007/bf01277661
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological evidence for visuocognitive dysfunction in younger non caucasian patients with Parkinson's disease

Abstract: A study of "primary" (VEPs) and "cognitive" (ERPs) visual evoked potentials was carried out in a group of non-demented Afro-American Parkinson's disease (PD) patients. Current studies suggest that differences exist in the clinical manifestations of PD in Caucasian and non-Caucasian populations. Two horizontal sinusoidal gratings differing in spatial frequency, i.e., 1 and 4 cycles per degree (cpd), were presented in an "odd-ball" paradigm to 17 patients with PD and 17 age-matched control subjects. While the 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 31 publications
0
10
0
3
Order By: Relevance
“…A clear relationship between motor subtype and NPS has not been reported previously, but our findings need to be verified through longitudinal analyses because of possible instability in motor subtyping in early PD. The association between race and NPS or cognition in PD has not been well explored, although some evidence exists that cognitive deficits and dementia are more common in nonwhite PD patients, and that nonwhites receive lower quality of depression treatment compared with whites . No difference was found between white and nonwhite PD patients for age, sex, education, MDS‐UPDRS Part III score, TD versus non‐TD subtype, or PD duration that would have helped explain the differences in NPS (data not shown).…”
Section: Discussionmentioning
confidence: 98%
“…A clear relationship between motor subtype and NPS has not been reported previously, but our findings need to be verified through longitudinal analyses because of possible instability in motor subtyping in early PD. The association between race and NPS or cognition in PD has not been well explored, although some evidence exists that cognitive deficits and dementia are more common in nonwhite PD patients, and that nonwhites receive lower quality of depression treatment compared with whites . No difference was found between white and nonwhite PD patients for age, sex, education, MDS‐UPDRS Part III score, TD versus non‐TD subtype, or PD duration that would have helped explain the differences in NPS (data not shown).…”
Section: Discussionmentioning
confidence: 98%
“…In consequence, we can suggest that the reduction of amplitudes and selective slowing of the cortical activity is the result of altered brain processing. This has also been proposed for Parkinson's disease [24]. However, we cannot reject a possible parallel impairment to the retina.…”
Section: M-vep C8°°nmentioning
confidence: 93%
“…8 Reduced amplitudes and increased latencies of visual evoked potentials have been reported in PD. [9][10][11][12] Electroretinography showed reduced a-and b-wave amplitudes indicating that retinal alterations are likely to contribute to changes in visual function. 10,13 Moreover, Ikeda et al 11 found a delay in the light peak in electrooculography reflecting reduced function of RPE.…”
mentioning
confidence: 99%